LITERARY ANALYSIS OF THE DEPICTION OF THE IMAGE OF AMIR TEMUR IN “THE FAREWELL OF MOTHER HAWK” WRITTEN BY PIRIMKUL KADYROV - Pulatova Mohichehra Temirovna (Journals Park Publishing, 2024)
This article explores the depiction of the image of Amir Temur in “The farewell of mother hawk” written by Pirimkul Kadyrov and analyses the correlation of real facts and imagination with examples.
Keywords: Literary analysis, military campaigns, horse fencing, golden stamp, historical truth.